2020
DOI: 10.1002/adma.202002439
|View full text |Cite
|
Sign up to set email alerts
|

GSH‐Depleted Nanozymes with Hyperthermia‐Enhanced Dual Enzyme‐Mimic Activities for Tumor Nanocatalytic Therapy

Abstract: As prospective alternatives for natural enzymes, catalytically active nanomaterials, known as "nanozymes" have attracted considerable interest over the past decade owing to their obvious

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
396
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 481 publications
(402 citation statements)
references
References 58 publications
3
396
2
1
Order By: Relevance
“…Generally, the size of nanoparticle directly determines the relative amounts of cerium ions Ce 3+ and Ce 4+ , and the proportion of Ce 3+ ions in CeO 2 NPs increases with the decrease of particle size. [ 5,6 ] However, the ultrasmall CeO 2 NP nanozymes are vulnerable to aggregation and then the nanozyme activities are dramatically reduced. [ 6 ] Therefore, the stability and aggregation of ultrasmall CeO 2 NPs are very significant for improving their enzyme‐like activities.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the size of nanoparticle directly determines the relative amounts of cerium ions Ce 3+ and Ce 4+ , and the proportion of Ce 3+ ions in CeO 2 NPs increases with the decrease of particle size. [ 5,6 ] However, the ultrasmall CeO 2 NP nanozymes are vulnerable to aggregation and then the nanozyme activities are dramatically reduced. [ 6 ] Therefore, the stability and aggregation of ultrasmall CeO 2 NPs are very significant for improving their enzyme‐like activities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34–39 ] High valence manganese as a simulated catalase has been applied for alleviating tumor hypoxia by decomposing H 2 O 2 to produce H 2 O and O 2 , which could also catalyze the transformation of reduced GSH into oxidized glutathione (GSSG) providing its properties of glutathione peroxidase. [ 40 ]…”
Section: Introductionmentioning
confidence: 99%
“…Various Fe-doped nanoplatforms have been reported to catalyze the conversion of endogenous H 2 O 2 to O 2 and thus could enhance the therapeutic effects against hypoxic tumor, including Fe-doped polydiaminopyridine nanofusiforms (Fe-PDAP) (Bai et al, 2018), Fe III doped C 3 N 4 nanosheets , and Fe 3+ -driven assembly of fluorenylmethyloxycarbonyl (Fmoc) protected amino acids (Fmoc-Cys/Fe) . Lan et al (2018) Prussian blue (PB), a clinical medicine approved by U.S. FDA for the treatment of radioactive exposure, has been proven with catalase-like activity (Cai et al, 2016;Zhou et al, 2018 (Dong et al, 2020), RuO 2 (Huang et al, 2020;Xu et al, 2020), V 2 O 5 , mesoporous manganese cobalt oxide derived from MOFs (Wang et al, 2019), Pd@Pt nanoplates (Wei et al, 2018), gold nanoclusters (Liu, C. P., et al, 2017), MOF-Au nanohybrid (He et al, 2019), Pt nanoparticles decorated on MOFs (Zhang et al, 2018), Pt-based core-shell nanoplatform (Wang X. S. et al, 2018), two-dimensional Pd@Au bimetallic core-shell nanostructure , etc. By taking the advantage of dual enzyme-mimic catalytic activity of ultrasmall CeO 2 , Dong et al (2020) fabricated a nanocomposite with hyperthermiaenhanced peroxidase-like activity, catalase-mimic activity, and GSH depletion for efficient tumor therapy in the NIR-II window.…”
Section: Hydrolysis Of Exogenous Peroxide To Produce Omentioning
confidence: 99%
“…Lan et al (2018) Prussian blue (PB), a clinical medicine approved by U.S. FDA for the treatment of radioactive exposure, has been proven with catalase-like activity (Cai et al, 2016;Zhou et al, 2018 (Dong et al, 2020), RuO 2 (Huang et al, 2020;Xu et al, 2020), V 2 O 5 , mesoporous manganese cobalt oxide derived from MOFs (Wang et al, 2019), Pd@Pt nanoplates (Wei et al, 2018), gold nanoclusters (Liu, C. P., et al, 2017), MOF-Au nanohybrid (He et al, 2019), Pt nanoparticles decorated on MOFs (Zhang et al, 2018), Pt-based core-shell nanoplatform (Wang X. S. et al, 2018), two-dimensional Pd@Au bimetallic core-shell nanostructure , etc. By taking the advantage of dual enzyme-mimic catalytic activity of ultrasmall CeO 2 , Dong et al (2020) fabricated a nanocomposite with hyperthermiaenhanced peroxidase-like activity, catalase-mimic activity, and GSH depletion for efficient tumor therapy in the NIR-II window. Huang et al (2020) reported that a multifunctional artificial metalloprotein nanoanalogue, RuO 2 -hybridized ovalbumin (OVA) nanoanalogues, not only exhibited photothermal/ photodynamic effect under NIR light irradiation but also effectively alleviated tumor hypoxia via catalysis of intracellular H 2 O 2 to produce O 2 , thereby concurrently enhancing PDT and reversing the immunosuppressive TME.…”
Section: Hydrolysis Of Exogenous Peroxide To Produce Omentioning
confidence: 99%